ANALISIS PENGARUH DEBT FINANCING DAN EQUITY FINANCING TERHADAP PROFIT EXPENSE RATIO PADA PERBANKAN SYARIAH JAMBI PERIODE 2003-2010 - Arna Suryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
In accordance with the mission of Islamic banking as an institution budging in Islamic banking, the Bank syariah mandiri play an active role in running an independent intermediary function, through the funding of community and channel it back to the community in the form of financing. While walking on the path to Islamic principles but the Bank Syariah Mandiri still want to profit as much as possible in assessing its performance in accordance with Islamic principles that have been determined. This can be evidenced by the profit generated bank syariah mandiri in 2009 is 196.415.940 rupiah and 2010 is 290.942.628 rupiah.In this research, the author uses descriptive method with approach of associative and quantitative methods. For statistical calculations the authors use the computer program SPSS version 16.0. The analysis tool used is multiple linear regression analysis, the classical assumption test, multiple correlation analysis, analysis of determination t test, F test, and partial correlation analysis.Based on the findings that partial regression coefficient of variable rate debt financing and equity financing to produce the level of -0.166 and -0.374 means that a negative effect on profit or expense ratio is inversely proportional. If the level of debt financing and equity financing levels have increased, the expense ratio will decrease profits. And vice versa, if the level of debt financing and equity financing rate has decreased, the expense ratio will increase profit.Thus the authors conclude that the influence between the level of debt financing and equity financing to the profit level of expense ratio is negatively affected and there a weak association between the independent variable on the dependent variable.Key word : Debt financing, Equity financing, Profit expence Ratio